Household food insecurity in rural and urban West Java: The need for coping strategies - Vipta Resti Mauludyani Anna; Khomsan Ali (BIO Web of Conferences)
To meet dietary demands and avoid nutritional issues, households experiencing food insecurity employ coping strategies. This study evaluated the degree of food insecurity and coping mechanisms used by households in rural and urban West Java. Using pretested questionnaires, this cross-sectional study collected data from 300 households in rural Cianjur and urban Sukabumi in June 2022. In both places, most households experience food insecurity (rural 70.0%, urban 63.3%). Nonetheless, relying on less-priced and less favored items was the most common coping technique among food-insecure households in both regions. Relying on less preferred and less expensive food was significantly more common in rural areas (40.7%) than urban areas (23.3%). Furthermore, a substantially greater proportion of rural households (19.3% vs. 10.0%) borrowed food or turned to friends or family for support. Overall, the occupation of the father, the level of education of the mother, and the percentage of food spending were the factors that determined household food insecurity. In conclusion, this study suggests that food-insecure households in rural and urban areas employ different coping mechanisms. Urban areas can gain advantages from subsidized food initiatives, while rural regions benefit more from agricultural support tailored to local communities.